To the problem of Source Base Systematization of the Theory, History and Practice of Family Education Study - Valentyna Fedyaeva (Pedagogical Discourse, 2013)
The article is a brief summary of the results of research on the problem of source base systematization of the theory, history and practice of children’s education in the family in the modern historical and pedagogical science. The article presents the specific aspects of the theoretical study of certain questions of family education in different scientific areas: philosophy, history, sociology, familistics, demography, economics, law, psychology, pedagogy, medicine, ethnography etc. The author analyzes the origins of the formation of the child's upbringing in the family theoretical foundations a as a historical and pedagogical problems, the sources of its research and their classification; the systematization groups of scientific works on a direction and the problem of research of the national historical and pedagogical discourse is represented.